2012
DOI: 10.1007/s00213-012-2645-9
|View full text |Cite
|
Sign up to set email alerts
|

MDMA enhances “mind reading” of positive emotions and impairs “mind reading” of negative emotions

Abstract: The shift in the ability to correctly read socioemotional information toward stimuli associated with positive emotional valence, together with the prosocial feelings elicited by MDMA, may enhance social approach behavior and sociability when MDMA is used recreationally and facilitate therapeutic relationships in MDMA-assisted psychotherapeutic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
160
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(189 citation statements)
references
References 49 publications
26
160
3
Order By: Relevance
“…Thus, MDMA mainly seems to enhance pleasure in touching and physical closeness rather than actual sexual engagement and is also reported to impair sexual performance (Frohmader et al, 2010;Passie et al, 2005;Theall et al, 2006;Zemishlany et al, 2001). Neurochemically, MDMA enhances 5-HT and NE and weakly also DA transmission (Hysek et al, 2012b) but additionally, MDMA also releases oxytocin and prolactin (Hysek et al, 2012a;Hysek et al, 2013). Dopamine, NE and oxytocin enhance and 5-HT and prolactin inhibit sexual excitation Pfaus, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MDMA mainly seems to enhance pleasure in touching and physical closeness rather than actual sexual engagement and is also reported to impair sexual performance (Frohmader et al, 2010;Passie et al, 2005;Theall et al, 2006;Zemishlany et al, 2001). Neurochemically, MDMA enhances 5-HT and NE and weakly also DA transmission (Hysek et al, 2012b) but additionally, MDMA also releases oxytocin and prolactin (Hysek et al, 2012a;Hysek et al, 2013). Dopamine, NE and oxytocin enhance and 5-HT and prolactin inhibit sexual excitation Pfaus, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MDMA has been shown to acutely alter related components of social cognition including recognition of facial emotions (Bedi et al, 2010;Hysek et al, 2012a;Hysek et al, 2013;Hysek et al, 2014;Kirkpatrick et al, 2014) and emotional empathy (Hysek et al, 2013;Kuypers et al, 2014;Schmid et al, 2014). Additionally, changes in 5-HT levels may influence cognitions sustaining intimate relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Because 125 mg MDMA did not alter overall mind reading accuracy (Hysek et al, 2012a) or cognitive empathy (Hysek et al, 2013) we did not expect that 75 mg MDMA would produce general impairments in cognitive empathy or ToM (Hysek et al, 2012a;Hysek et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…For example, our laboratory investigated the mode of action of MDMA in humans by blocking the NET, SERT, or DAT or combinations thereof (Hysek et al, 2011;Hysek et al, 2012c;Hysek et al, 2014;Liechti et al, 2000;Schmid et al, 2014;Schmid et al, 2015). These studies showed that NET and α 1 -adrenergic stimulation are crucially involved in MDMA-induced sympathomimetic activation, including elevations of blood pressure and body temperature (Hysek et al, 2012a;Hysek et al, 2013;Hysek et al, 2011;Schmid et al, 2015) and that the SERT-mediated release of 5-HT is involved in the subjective entactogenic/empathogenic effects of MDMA (Hysek et al, 2012b;Hysek et al, 2012c;Liechti et al, 2000). Interactions with the DAT and activation of the DA system are generally considered responsible for the reinforcing and addictive properties of a substance (Howell & Wilcox, 2002).…”
Section: Methods For Studying Transporter and Receptor Pharmacology Imentioning
confidence: 99%